2002
DOI: 10.1126/science.1069270
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Recent Southern Hemisphere Climate Change

Abstract: Climate variability in the high-latitude Southern Hemisphere (SH) is dominated by the SH annular mode, a large-scale pattern of variability characterized by fluctuations in the strength of the circumpolar vortex. We present evidence that recent trends in the SH tropospheric circulation can be interpreted as a bias toward the high-index polarity of this pattern, with stronger westerly flow encircling the polar cap. It is argued that the largest and most significant tropospheric trends can be traced to recent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

134
1,527
7
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,702 publications
(1,720 citation statements)
references
References 38 publications
134
1,527
7
22
Order By: Relevance
“…A better understanding of factors influencing SH blocking characteristics is desirable, even more so in light of strengthened westerlies due to a robust upward trend in the southern annular mode (e.g., Thompson and Solomon 2002), a weakening of the split jet in the region in recent decades (Bals-Elsholz et al 2001), reduced blocking activity , and decreases in cutoff low rainfall across southern regions of Australia Risbey et al 2013). To usefully assess future projected changes in midlatitude blocking and, by inference, rainfall projections in those regions where blocking is an important driver, improvement in the representation of atmospheric blocking in state-of-theart GCMs is thus crucial, especially given that blocking can be considered an ''emergent phenomenon created indirectly by dynamical and physical processes in the model.…”
Section: Resultsmentioning
confidence: 99%
“…A better understanding of factors influencing SH blocking characteristics is desirable, even more so in light of strengthened westerlies due to a robust upward trend in the southern annular mode (e.g., Thompson and Solomon 2002), a weakening of the split jet in the region in recent decades (Bals-Elsholz et al 2001), reduced blocking activity , and decreases in cutoff low rainfall across southern regions of Australia Risbey et al 2013). To usefully assess future projected changes in midlatitude blocking and, by inference, rainfall projections in those regions where blocking is an important driver, improvement in the representation of atmospheric blocking in state-of-theart GCMs is thus crucial, especially given that blocking can be considered an ''emergent phenomenon created indirectly by dynamical and physical processes in the model.…”
Section: Resultsmentioning
confidence: 99%
“…Model simulations provide a way to help elucidate the link between climate variability and sea-ice variability and trends. As previous studies have suggested that the Southern Annular Mode (SAM) 21,22 , the El Niño Southern Oscillation (ENSO) 23,23 and the weather 24,25 may all be important factors in sea-ice variability and trends, a study to assess the dominant drivers is needed.…”
mentioning
confidence: 99%
“…Recent warming over the Antarctic Peninsula has been explained in part by a positive trend in the Southern Annular Mode (SAM), manifested as a strengthening of the circumpolar westerlies, and attributed to stratospheric ozone depletion and increasing greenhouse gases 6,7 . The SAM does not readily account for warming in continental West Antarctica, however, because increased westerlies tend to cool, rather than warm, the Antarctic interior 8,9 .…”
mentioning
confidence: 99%